Manufacturing of protein concentrate from the flesh of snakehead fish (Channa striata) through consecutive ultrasound-assisted organic solvent extraction and vacuum drying - Kumoro, Andri Cahyo; Wardhani, Dyah H.; Kusworo, Tutuk D.; Djaeni, Mohamad; Azis, Yusuf Ma’rifat Fajar; Alhanif, Misbahudin; Ping, Tan Chin (Taylor and Francis Group, 2023)
Fish protein concentrate (FPC) is considered as a promising alternative to overcome the world’s shortage of affordable animal-based protein. Snakehead fish (Channa striata) offers a large potential as a raw material for FPC manufacture. This work aims to investigate the influence of solvent types (ethanol, n-hexane, and an azeotrope mixture of ethanol + n-hexane), extraction time (0, 10, 15, 20, 25, and 30 minutes), temperature (30, 40, 50, and 60°C), liquid solvent volume to solid feed fish flesh mass ratio (LSSFR) (1, 2, 3, 4, 5, 6, and 7 mL/g), and ultrasonic power (100, 200, 300, and 400 W) on the ultrasound-assisted extraction (UAE) to manufacture high-quality FPC from snakehead fish. After being subjected to UAE, the fish flesh was filtered and dried under reduced pressure at 55°C. The optimum UAE conditions for the manufacture of FPC from snakehead fish flesh were using ethanol as solvent, LSSFR (6 mL/g), temperature (40°C), ultrasonic power (200 W), and extraction time (25 minutes). The resulted FPC can be categorized as type A, which contains protein (73.17%) and fat (0.73%). An SDS-PAGE electrophoresis evaluation proved that the FPC contained 12 types of peptides having molecular weight (MW) ranging from 4.00 to 174.00 kDa with the major fractions being those with MWs ranged from 4.00 to 11.00 kDa and the minor fractions with MWs between 71.70 to 174.00 kDa. Indeed, the presence of both low and high MW peptides in the FPC indicates its potential applications in the development of nutritious food products.